Enhancing anti-corruption character through VBL on response text: A case study - Arumtyas Puspitaning Padmasari; Aqiel Ajiz Alfaris; Renda Aranggraeni; Dedi Setiawan; Victor Mt. L. Tobing; Nuril Huda; Daniel Arseneault (Research and Development in Education (RaDEn), 2025)
Corruption poses a significant challenge in Indonesia, adversely affecting various sectors, including the economy, politics, education, and society at large. Corruption has become ingrained as a culture, character, and mindset within Indonesian society, a phenomenon inherited since the colonial era. This study investigates the effectiveness of video-based learning through short films in enhancing response text about anti-corruption character education for 7th-grade junior high school students in Sidoarjo. It also aims to analyze the impact of the video-based learning method on students' understanding of anti-corruption values and to identify the supporting and inhibiting factors for its implementation. The qualitative research employs a case study approach, focusing on 30 students writing in Response text after watching the short film "RAPOR". This research uses observation, interview, survey, and supporting document for analysing research data. Using categoriation table and graphic are helping the research validation. Findings indicate that video-based learning significantly improves students' understanding of response text which mentions and argues anti-corruption values, enhances critical thinking skills, and fosters discussion engagement. Key supporting factors include the interactive nature of short films, which makes moral lessons more relatable while inhibiting factors encompass limited access to quality educational films and the need for adequate time and resources for analysis. Overall, the study underscores the potential of video-based methods to effectively instill integrity-driven values in the younger generation, thereby contributing to the long-term goal of reducing corruption in Indonesia. Recommendations for educational strategies to improve access and implementation of video-based learning are provided to maximize its impact on character education.